Organization and conducting methods of physical education lessons in general education schools (SCIENCE and SOCIETY, 2026)
The article examines the issues of the structure of a physical education lesson, the creation of hygienic conditions for conducting a lesson, the solution of various pedagogical problems, issues of comparison of parts of the lesson conducted with schoolchildren of different ages. The psychological and physiological characteristics of primary school children are also examined.